2012
DOI: 10.1371/journal.pone.0030658
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Pattern of Local Adaptation during an Experimental Heat Wave in a Pipefish-Trematode Host-Parasite System

Abstract: Extreme climate events such as heat waves are expected to increase in frequency under global change. As one indirect effect, they can alter magnitude and direction of species interactions, for example those between hosts and parasites. We simulated a summer heat wave to investigate how a changing environment affects the interaction between the broad-nosed pipefish (Syngnathus typhle) as a host and its digenean trematode parasite (Cryptocotyle lingua). In a fully reciprocal laboratory infection experiment, pipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 57 publications
3
23
0
Order By: Relevance
“…; Landis et al. ; Sentis et al. ) is the simulation of heat wave conditions in laboratory, with different severity levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Landis et al. ; Sentis et al. ) is the simulation of heat wave conditions in laboratory, with different severity levels.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the complexity of insect response to climatic anomalies but also the stochasticity and unpredictability of such anomalies, and their localized occurrence in time and space, a wide range of experiments can be conducted (Jentsch et al 2007). The approach that has been used here but also in other recent studies (e.g., Sorte et al 2010;Gillespie et al 2012;Landis et al 2012;Sentis et al 2013) is the simulation of heat wave conditions in laboratory, with different severity levels. Although this method does not allow reproducing exactly what happens outdoors, it allows exploring some mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In ectothermic animals, such as fish, the activity and efficiency of their immune systems is strongly temperature dependent (Ellis 2001). At the same time, metabolic rates and virulence traits of parasites are influenced and temperature is thought to be a strong modifier of host-parasite interactions (Lazzaro & Little 2009;Studer, Thieltges & Poulin 2010;Landis et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In an experimental test, Landis et al. (2012) showed that an increase in water temperature decreased the proportion of innate immune cells in infected host pipefish ( Syngnathus typhle ). The results of this experiment indicates that there is a strong host × parasite × environment interaction that may affect the genes that play major roles in parasite defense such as MHC genes.…”
Section: Introductionmentioning
confidence: 99%